Hello There
Its pretty tricky but here is your answer
<span>4833.977
Want full answer? here
</span>
<span>4833.97738
Good luck brainy
</span>
Step-by-step explanation:
3y + x = 12
When y = 3, we have 3(3) + x = 12.
=> 9 + x = 12, x = 3.
Answer:
Step-by-step explanation:
(1,-4) is the answer reason why is you add the equations in order to solve for the first variable plug it in the equations in order to solve for the remaining variables
Answer: -4/5
Step-by-step explanation:
you can use slope formula to solve this question. (Y1-Y2)/(X1-X2). So the answer to this question should be (0-4)/(5-0)= -4/5